Russian Constitutional Development: Formal and Informal Practices - A. Medushevskiy (BRICS Law Journal, 2019)
Transitional constitutionalism remains the subject of intensive political controversy. Based on a project made possible by the Institute of Law and Public Policy (Moscow) this article presents the analysis of the basic constitutional principles of pluralism, the separation of powers, federalism, the independence of the judiciary and the guarantee of political rights and freedoms. It describes the changing character of their implementation in different areas of constitutional practices – legislation, constitutional justice, administrative activities and informal practices, and the comparative level of constitutional deviations in each of them. The important new expertise of this research is the concept and methodology of the constitutional monitoring and recommendations for full-scale reforms in key areas of Russian constitutional and political settlement. The author shows that the true choice facing modern society is not between constitutionalism or its negation, which is a dilemma, but between real and sham constitutionalism, with a wide variety of intermediate options separating them. It is precisely this intermediate area which the author defines as a transitional type of constitutionalism, the field of collision between different political stakeholders. This is an area of unstable equilibrium where the implementation of different legal strategies and technologies may produce a definitive effect.